2001
DOI: 10.4269/ajtmh.2001.65.242
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Japanese encephalitis virus: envelope gene based analysis reveals a fifth genotype, geographic clustering, and multiple introductions of the virus into the Indian subcontinent.

Abstract: Abstract. We report the analysis of the complete nucleotide sequence for the Indian isolate (P20778; Genbank Accession number AF080251) of Japanese encephalitis virus (JEV). The phylogenetic tree topology obtained using thirteen complete genome sequences of JEV was reproduced with the envelope, NS1, NS3, and NS5 genes and revealed extensive divergence between the two Indian strains included. A more exhaustive analysis of JEV evolution using 107 envelope sequences available for isolates from different geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 44 publications
1
108
0
1
Order By: Relevance
“…2,3 On the basis of nucleotide sequence information for the E gene, JEV has been divided into five genotypes. 4,5 Japanese encephalitis virus is a mosquito-borne virus and Culex tritaeniorhynchus mosquitoes are the most important vector of JEV in Japan. The virus exists in an enzootic cycle between mosquitoes and either pigs or birds.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 On the basis of nucleotide sequence information for the E gene, JEV has been divided into five genotypes. 4,5 Japanese encephalitis virus is a mosquito-borne virus and Culex tritaeniorhynchus mosquitoes are the most important vector of JEV in Japan. The virus exists in an enzootic cycle between mosquitoes and either pigs or birds.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses based on nucleotide sequences of prME, NS1 and full length genes revealed that JEVs worldwide were classified into 5 genotypes (genotype 1, 2, 3, 4 and 5) (Solomon et al, 2003;Nitatpattana et al, 2008;Uchil and Satchidanandam, 2001). In this study, phylogenetic analysis based on the nucleotide sequences of the prME genes indicated that five commercial vaccine strains showed a close relationship with the Anyang 300 strain grouping the genotype 3.…”
Section: Discussionmentioning
confidence: 85%
“…The occurrence of JEV genotypes I and III in northern regions and II and IV in southern regions led to the proposal that different genotypes may explain the differing clinical epidemiology (Chen et al, 1990(Chen et al, , 1992. However, the recent arrival of a 'northern genotype I' isolate in Australia (Pyke et al, 2001), the observation that genotype III is associated with epidemic disease in northern Vietnam and endemic disease in southern Vietnam (Solomon et al, 2000a), and the idenitification of a putative V genotype (Uchil and Satchidanandam, 2001) suggest the current paradigm may need revising.…”
Section: Clinical Epidemiologymentioning
confidence: 99%